Attention-Deficit/Hyperactivity Disorder, Behavior Regulation and Virtual School Support. Issue 3 (April 2016) - Wallace, Claire; Ievers-Landis, Carolyn E.; Scherer, Catherine; Roizen, Nancy; Augustyn, Marilyn
Abstract : CASE: Tony is a 6-year-old multiracial boy diagnosed as having attention-deficit/hyperactivity disorder—combined type who is followed in your primary care practice and has started on a stimulant medication. Tony continues to have difficulty with emotion regulation and impulse control both at home and at school. He was asked to leave his private school soon after beginning first grade because of physical fighting, emotional outbursts, and arguing with teachers. His mother made the decision to enroll Tony in online virtual schooling for the remainder of the academic year, with the plan to transition back to traditional school for the next academic year. They have enrolled in a program that offers lessons online and sends materials to the home for the child to use to complete certain types of assignments (e.g., science experiments). Virtual schools are different from traditional home schooling because children receive their instruction from teachers online with parental assistance as opposed to parents being responsible for teaching all material. Tony's mother comes to your practice requesting assistance with setting up an appropriate school environment for her son at home, where she can monitor and support his academic progress. Tony is a bright child, with an Intelligence Quotient in the superior range. He has advanced academic skills, but he becomes dysregulated if he is told he is wrong or that he has answered a question incorrectly. For example, if he answered a question incorrectly in class, he would become verbally abusive toward his teacher and often have temper tantrums. This challenging behavior occurred daily at school and was one of the factors leading to his expulsion. The behavior had predated the introduction of stimulant medication and had remained consistent after he began medication. Tony's parents are highly educated, and both parents hold professional jobs with steady income. His parents have good command of typical behavior management strategies such as the use of rewards, time out, and behavioral contingencies to target noncompliance and temper tantrums. However, Tony's difficulty identifying and regulating his emotions leads to emotional outbursts and shutdowns that have thus far been unresponsive to standard behavior management techniques. Tony continued to have outbursts even when the behavior was ignored. His mother is concerned not only about his learning during the coming year but also about his social relationships and the family dynamic. Tony's outbursts cause significant disruption in the home and are a source of tension among parents and siblings. His mother is asking for advice on how to support his behavior better at home now that he will be spending his entire day there. How might you assist this child and his mother by helping to integrate therapeutic goals into the academic environment?